DIVINE DEMANDS FOR JUSTICE: AN EXEGETICAL READING OF AMOS 5, 18-27 - HALEK BERE, PAULUS (Jurnal Teologi (Journal of Theology), 2023)
The book of Amos is one of the prophetic literatures to be read in every context of human life. While reading Amos 5,18-27 we may ask the question: What is the reason for God to hate Israel’s worship and not accepting their offering? This selected text shows a contrasting movement of relationship between God and Israel. God chooses and makes Israel his own, in order that they would be an instrument of his blessing for others. However, the Israelites failed to practice it in their daily life. In this exegetical paper, I would suggest that neglecting justice for the poor in the society provokes God’s anger to hate Israel’s worship and reject their sacrifice.  Concerning the wickedness of Israel, Amos declared that even though Israel desires for the day of Yahweh, it is darkness and not light for them (v.18) and because of their sins, God will send them into exile beyond Damascus (v. 27). God hates their attitude but still loves them as his chosen people. The purpose of Amos’s announcement is to change the hearts of ruling class’s behavior and his basic concern on socioeconomic injustices. Amos’s oracles suggest that the officials got rich in dishonesty. The exile is the consequence of the failure of Israel leaders in leading the people to live in divine will. It becomes the moment for Israel to purify themselves before God and being trained for strengthen their good relationship with Yahweh, their God.